1996
DOI: 10.1080/01448765.1996.9754763
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Efficient VA Mycorrhizal Fungi for Papaya

Abstract: Papaya (Carica papaya L.) is an important tropical fruit tree. Thirteen different mycorrhizal fungi were screened for their symbiotic efficiency with papaya. Of the 13 fungi tested Glomus mosseae (ICRISAT) was found to be the best fungus for improving growth and nutrition of papaya resulting ·in a greater plant biomass, plant height, plant girth, leaf area, P and Zn content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The most significant response was exhibited in plants inoculated with G. mosseae. These observations support the earlier findings of Reddy et al (1996) who reported that G. mosseae (ICRISAT) was the most efficient fungus for improving plant biomass of papaya plants. Jaizme-Vega and Azcoñ (1995) reported G. fasiculatum to be the most efficient fungus in improving growth of papaya, pineapple and banana under green house and field conditions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The most significant response was exhibited in plants inoculated with G. mosseae. These observations support the earlier findings of Reddy et al (1996) who reported that G. mosseae (ICRISAT) was the most efficient fungus for improving plant biomass of papaya plants. Jaizme-Vega and Azcoñ (1995) reported G. fasiculatum to be the most efficient fungus in improving growth of papaya, pineapple and banana under green house and field conditions.…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with the work of Plenchette et al (1981) and Reddy et al (1996) who reported similar growth response in apple and papaya inoculated with arbuscular mycorrhizal fungi grown in unsterile acidic soil with similarly low levels of phosphorus. The study also supports the findings of Onkarraya and Mohandas (1993) that presented improved height and root length of mycorrhizal Citrus under similar set of experimental conditions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A study by Michel-Rosales and Valdés 19 and Reddy, et al . 20 revealed colonization of C. aurantifolia roots with several arbuscular mycorrhizae. Mycorrhizae is common in the roots of several citrus species and it contributes to enhancing tolerance of citrus plants to drought, salinity, high temperature and diseases 17 , 18 , 30 – 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Gerdemann and Trappe obtained from the University of Western Australia, Nedlands, Australia containing 1,736 infective propagules/g was used for papaya. These AM fungi were chosen as they were effective fungi for the two perennials in earlier studies (Balakrishna Reddy et al 1996;Umakanth and Bagyaraj 1998).The most probable number method with 10-fold dilution was used for estimating the number of infective propagules (Porter 1979). The AM fungi used were maintained at the Department of Microbiology, University of Agricultural Sciences, Bangalore, India in a sterilized sand: soil mixture (1:1 by volume) with Rhodes grass (Chloris gayana L.) as host.…”
Section: Methodsmentioning
confidence: 99%